Wheelchair sport: Pushing from Atlanta to Rio . the sports science journey - Goosey-Tolfrey, V. L. (Japanese Journal of Physical Fitness and Sports Medicine, 2016)
In order to develop and implement safe and effective training programmes for a wheelchair athlete an understanding of the physical impairment is essential. This article will focus on the wheelchair athlete to describe how the training prescription for the nondisabled may be challenged in terms of its use for athletes with a spinal cord injury (SCI); describe the approach taken to optimise wheelchair set-up and finally describe how a multi-disciplinary sports science team prepares athletes for competition in the heat.